Zombie board: Board tenure and firm performance [Summary of paper] - HUANG, Sterling (Institutional Knowledge at Singapore Management University, 2013)
In my paper, Zombie Boards: Board Tenure and Firm Performance, which was recently made publicly available on SSRN, I empirically investigate how board tenure is related to firm performance and corporate decisions, holding other firm, CEO, and board characteristics constant. I find that board tenure has an inverted U-shaped relation with firm value, and that this curvilinear relation is reflected in M&A performance, financial reporting quality, corporate strategies and innovation, executive compensation, and CEO replacement. The results indicate that, for firms with short-tenured boards, the marginal effect of board learning dominates entrenchment effects, whereas for firms that have long-tenured boards, the opposite is true. The analysis relies on the assumption that some transaction costs prevent boards from fully adjusting to their optimal tenure level. But what are those transaction costs? For long-tenured boards, transaction costs could take the form of agency costs. For instance, board tenure choice may reflect the extent to which CEOs have influence over the board selection process (Hermalin and Weisbach, 1998). Further, firms with staggered boards can only replace a portion of board member each year, in which case the use of a staggered board itself introduces agency problems (Bebchuk and Cohen, 2005). For short-tenured boards, transaction costs could take the form of frictions in the labor market for directors.